2019
DOI: 10.1097/mop.0000000000000812
|View full text |Cite
|
Sign up to set email alerts
|

Vascular malformations syndromes: an update

Abstract: Purpose of review To provide an update of vascular malformation syndromes by reviewing the most recent articles on the topic and following the new International Society for the Study of Vascular Anomalies (ISSVA) 2018 classification. Recent findings This review discusses the main features and diagnostic approaches of the vascular malformation syndromes, the new genetic findings and the new therapeutic strategies developed in recent months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 41 publications
0
52
0
5
Order By: Relevance
“…The International Society for the Study of Vascular Anomalies (ISSVA; https://www.issva.org) published the ISSVA classification for VA in 2014 and revised version in 2018, which classifies VA into two large categories of vascular tumors and vascular malformations. [1][2][3][4][5][6][7] Vascular tumors are defined as vascular neoplasms caused by the proliferation and hyperplasia of abnormal endothelial and other vascular cells, while vascular malformations are defined as congenital developmental disorders consisting of capillary, lymphatic, venous, and arterial vessel formation. [2][3][4][5][6][7][8][9][10] Vascular tumors feature increased endothelial turnover (mitosis), while vascular malformations do not.…”
Section: Introductionmentioning
confidence: 99%
“…The International Society for the Study of Vascular Anomalies (ISSVA; https://www.issva.org) published the ISSVA classification for VA in 2014 and revised version in 2018, which classifies VA into two large categories of vascular tumors and vascular malformations. [1][2][3][4][5][6][7] Vascular tumors are defined as vascular neoplasms caused by the proliferation and hyperplasia of abnormal endothelial and other vascular cells, while vascular malformations are defined as congenital developmental disorders consisting of capillary, lymphatic, venous, and arterial vessel formation. [2][3][4][5][6][7][8][9][10] Vascular tumors feature increased endothelial turnover (mitosis), while vascular malformations do not.…”
Section: Introductionmentioning
confidence: 99%
“…Other reported, but rare, symptoms include abdominal discomfort, abdominal pain, diarrhea, and perianal discomfort (2,8). CRVM may manifest as intestinal lesions in syndromic diseases, such as KTS, which is characterized by CRVM, skin capillary malformation, and asymmetric limb hypertrophy (13,14). In this study, two children showed multiple wine-like skin spots all over the body, complicated with asymmetric hypertrophy of both lower limbs, which was considered to be KTS.…”
Section: Discussionmentioning
confidence: 65%
“…7,31 The proliferative effect of PIK3CA mutations in PROS syndromes exhibits an apparent skewing in the pattern of affected tissues, with mesoderm-derived tissues (including vasculature and adipose tissue) being markedly affected. 32 Importantly, mosaic activating mutations in PIK3CA are also known to cause the majority of isolated lymphatic malformations (>90%) as well as a significant proportion of isolated venous malformations (25%-30%) in the nonsyndromic population 5,6,25 ; unrestrained activation of p110α in endothelial cells leads to a hyperproliferative phenotype and formation of vascular developmental tumors responsive to therapeutic PI3K inhibition. 25 Intermediate PROS phenotypes, characterized by capillary malformations with overgrowth and lipomatous neoformations, are often caused by PIK3CA mutations with intermediate oncogenic potency, including the p.E545A mutation that was detected in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The currently prevailing view is that, in contrast to other lipoma variants, ALs possess a normal karyotype and lack any distinctive chromosomal aberrations 3 . An association between sporadic AL and an overlying cutaneous capillary malformation has been reported 4 ; according to recent evidence, the pathogenesis of capillary malformations appears to be tightly linked to abnormal activation of the PI3K/AKT signaling pathway 5,6 . Interestingly, patients suffering from overgrowth syndromes caused by mosaic activating PIK3CA mutations (thus belonging to the PIK3CA‐related overgrowth spectrum, PROS) show a predisposition for the development of not only cutaneous vascular malformations but also benign proliferations of mature adipose tissue 7,8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation